Implementation of Business Intelligence to Analyze Product Popularity - Manalu, Evant Welsh; Hariyanto, Susanto (Komunitas Dosen Indonesia, 2026)
PT Dairyfood Internusa is a corporation engaged in the distribution of bakery products and food ingredients to Hotels, Restaurants, Cafes, and retail stores throughout Indonesia. This company conducts numerous transactions annually, resulting in a substantial amount of raw data that can be processed and analyzed to extract important information, which is then presented in visual form. Product popularity is one of many factors that determine the degree to which a product is liked and sought after by customers. It can be influenced by various factors, including its quality, social influence or marketing, and the availability of information about the product. And for this reason, a tool are needed to measure and visualize product popularity which can provide the stakeholder with necessary data that helps them in decision-making. The problem is how to make a system that can extract, transform, and visualize the data statistically in real time. The effort made is to cut labor and time for the users from transforming the raw data, by implementing the 9 Step Kimball methodology for developing a data warehouse which will be used to store the raw data and also the transformed data. Using the application Microsoft Power BI to enabled us to visualize the transformed, the author wants to create and design a business intelligence system that can make it easier for users or stakeholders to see and get the analytical data they needed in decision-making.